Tindak Tutur Ekspresif dalam Novel Ranah 3 Warna karya Ahmad Fuadi - Putri, Wanda Andita; Juita, Novia (Universitas Negeri Padang, 2024)
Research on expressive speech acts in novels is an important study to learn and understand. This research intends to discuss the types and functions of expressive speech in the novel Ranah 3 Warna by Ahmad Fuadi. The study of this novel is a descriptive method of qualitative research. The data of this research is in the form of characters' speech in the novel which relies on expressive speech acts. Data was collected using documentation techniques with the assistance of corpus linguistik technology, namely the korpus nusantara. The data was analyzed using computational linguistics technique through the stages of identification, classification, interpretation, and conclusion. This research found: (1) types of expressive speech acts: congratulating and thanking, expressing pleasure and anger, apologizing, praising, criticizing, insinuating, complaining, and insulting, (2) functions of expressive speech acts: convivial, collaborative, conflictive, and competitive functions.